PROJECT METHOD IN TECHNOLOGY AND IT EDUCATION - Noga, Henryk; Depešová, Jana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Based on the research it can be stated that both primary and junior high school students and teachers have different views on the effectiveness of project method used on technology and IT classes. The vast majority of students were the most satisfied with the practical classes that effectively combined theoretical and practical tasks. This form of work to a great extent fostered students’ activity. Unfortunately, although teachers were interested in using project method on technology and IT lessons, the way of using it can be questionable. Teachers emphasize the fact that not all issues can be achieved using this method.